2007
DOI: 10.1074/jbc.m610845200
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Glycolytic Flux in Saccharomyces cerevisiae Grown at Low Temperature

Abstract: Growth temperature has a profound impact on the kinetic properties of enzymes in microbial metabolic networks. Activities of glycolytic enzymes in Saccharomyces cerevisiae were up to 7.5-fold lower when assayed at 12°C than at 30°C. Nevertheless, the in vivo glycolytic flux in chemostat cultures (dilution rate: 0.03 h ؊1 ) grown at these two temperatures was essentially the same. To investigate how yeast maintained a constant glycolytic flux despite the kinetic challenge imposed by a lower growth temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 51 publications
7
65
0
Order By: Relevance
“…These data subsets were identical within experimental errors to corresponding metabolite pools obtained for glucose-growing CEN.PK 113-7D cells (data not shown), verifying that accumulation of metabolites was independent of pathway engineering. Values for glycolytic compounds, amino acids, AXPs, NAD(H), and NADP ϩ obtained for CEN.PK 113-7D grown on glucose under anaerobic conditions were in reasonable agreement with previous reports elsewhere (35,44,48,61,62 variations, and values between ϳ0.03 and 7.5 can be found in the literature (20,55). In these works, no 13 C-labeled internal standard was used (20,44,55), which together with different protocols used for quenching (55), extracting (20,44,55), or determination of NADPH concentration (44, 55) might be the reason for the observed discrepancies.…”
Section: Lc/ms-ms Analysissupporting
confidence: 92%
“…These data subsets were identical within experimental errors to corresponding metabolite pools obtained for glucose-growing CEN.PK 113-7D cells (data not shown), verifying that accumulation of metabolites was independent of pathway engineering. Values for glycolytic compounds, amino acids, AXPs, NAD(H), and NADP ϩ obtained for CEN.PK 113-7D grown on glucose under anaerobic conditions were in reasonable agreement with previous reports elsewhere (35,44,48,61,62 variations, and values between ϳ0.03 and 7.5 can be found in the literature (20,55). In these works, no 13 C-labeled internal standard was used (20,44,55), which together with different protocols used for quenching (55), extracting (20,44,55), or determination of NADPH concentration (44, 55) might be the reason for the observed discrepancies.…”
Section: Lc/ms-ms Analysissupporting
confidence: 92%
“…Using a rational approach to overproduce lactate, they generated a lactate dehydrogenase (LDH) that is catalytically more efficient. Moreover, it becomes increasingly obvious that several S. cerevisiae enzymes are regulated metabolically rather than by expression (40,66,188,338), a fact which future metabolic engineering strategies should take into account. A recent report suggests that even transcriptional regulators are subject to metabolic regulation.…”
Section: In Vivo Protein Activitymentioning
confidence: 99%
“…19,20) PK is a key regulatory enzyme in glycolysis, and is usually regulated under stressful conditions. [21][22][23] However, most studies have reported only a few genes for one or two metabolic reactions, which fails to explain the overall landscape of carbohydrate metabolic flows in plants. The different species and experimental conditions required for the regulation of genes are difficult to comprehend.…”
Section: Detection Of Sugar Accumulation and Expression Levels Of Cormentioning
confidence: 99%